1989
DOI: 10.1148/radiology.173.1.2675191
|View full text |Cite
|
Sign up to set email alerts
|

Calcification of the ductus venosus: a cause of right upper quadrant calcification in the newborn.

Abstract: The authors report three cases of ductus venosus calcification as an additional cause of vascular liver calcification in the newborn. All three infants had umbilical venous catheters. The calcification may be caused by extravasated fluids given through the catheter or by local trauma due to catheter insertion. An obliquely oriented, paravertebral "tram-track" calcification in the right upper quadrant, particularly in a premature infant with a history of umbilical venous catheterization, should suggest the diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This finding is thought to be secondary to mechanical stress causing sclerosis and calcification within the thickened venous intima and media. Calcification in the umbilical venous system/ductus venosus in infants after umbilical vein catheterization has also been documented, and similar hypotheses for etiology have been suggested [19,20]. Ultimately, only surgical exploration with pathologic evaluation can help define the true etiology of this unique finding.…”
Section: Discussionmentioning
confidence: 87%
“…This finding is thought to be secondary to mechanical stress causing sclerosis and calcification within the thickened venous intima and media. Calcification in the umbilical venous system/ductus venosus in infants after umbilical vein catheterization has also been documented, and similar hypotheses for etiology have been suggested [19,20]. Ultimately, only surgical exploration with pathologic evaluation can help define the true etiology of this unique finding.…”
Section: Discussionmentioning
confidence: 87%
“…Calcification associated with UVC is commonly observed in the liver [ 6 , 7 , 8 , 9 ]. However, regarding UVC-related calcification in the DV or UV, only two reports were previously published [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Calcification associated with UVC is commonly observed in the liver [ 6 , 7 , 8 , 9 ]. However, regarding UVC-related calcification in the DV or UV, only two reports were previously published [ 7 , 8 ]. Rizzo et al reported on calcification of the DV with a curvilinear appearance on X-ray images [ 7 ], caused by catheter-induced intimal injury and extravasation of calcium gluconate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The radiologic localization of calcifications to the structures of this compartment may be difficult (Lafortune 1990;Abu-Yousef 1990). A calcified ductus venosus associated with "tram-track" calcifications have been seen in neonates and suggested to be caused by catheterism (Rizzo et al 1989).…”
Section: Calcification Of Venous Vessels Of the Livermentioning
confidence: 99%